Using Problem-Based Learning to Boost Social Studies Performance: Classroom Action Research in Grade 5 at SD INPRES 3 Talise: English - Santika; Zulnuraini; Firmansyah, Arif; Muchdar (Jurnal Elementaria Edukasia, 2024)
The role of education in developing effective problem solvers, critical thinkers, and responsible members of society is of great importance. This research deals with the low performance in social studies subjects caused by the continued application of conventional teaching models. The aim of this study is to improve the learning outcomes of grade V students in social studies subjects at SD INPRES 3 Talise by applying the Problem-Based Learning (PBL) model. This classroom action research was conducted in two cycles, following the Kemmis and McTaggart model, involving 22 students from grade V. Data were collected through tests, observations, and interviews, then analysed quantitatively and qualitatively. Initial observations revealed that only 36.36% of students achieved the learning objectives with an average score of 50.90. The implementation of PBL involved the collaborative planning, action, observation, and reflection phases. The results demonstrated significant improvements in student engagement and learning outcomes. The average score increased, and the percentage of students who achieved the learning objectives rose significantly, respectively from 63.63 in cycle I to 81.59 in cycle II. However, the average score did not yet reach the KKM. Furthermore, the percentage of completeness has also increased, namely in cycle I by 59.09% and cycle II by 86.36%. This research demonstrates that PBL can effectively enhance the quality of social studies education by fostering learning.